Sovranit í e diritti umani: per uno spazio europeo dei diritti - Castaldo, Katia (Utopía y Praxis Latinoamericana, 1970)
In “times” of a profound crisis for public spaces, principally the crisis of sovereignty, collective identity, pertinence and radicalisms, Europe wishes to be a bastion of “resistance to globalization” and, as a whole, a space for affirming and guaranteeing the Rights that should be recognized for citizens through the language of politics. Starting from its long civilizing tradition, between dialog and openness, understanding sovereignty as the historical condition that makes Rights effective, Europe can be considered as a new political space that is not reduced to the “administration or management of bank accounts.” On the contrary, it is actually a political space for future projects that allow men to recover their capacity to think and create through symbols.